PERTANGGUNGJAWABAN YURIDIS DIREKSI TERHADAP RISIKO KERUGIAN KEUANGAN DAERAH PADA BADAN USAHA MILIK DAERAH - Tengku Erwinsyahbana (DE LEGA LATA: JURNAL ILMU HUKUM, 2017)
Activity which is taken and Regional Owned Enterprises (BUMD) may gives risks, both business risks and criminal implications. As an example taken in relating with a local company in Tanjungpinang City, whose ex-director was complained of a criminal act of corruption for causing financial losses in the management of PT. Tanjungpinang Makmur Bersama. It is interesting to be researched which the nature of the research is descriptive and the type of the is normative juridical with case approach. Based on the results of the analysis can be seen that the financial losses of regions in the implementation of management PT. Tanjungpinang Makmur together in Eva Amalia time as a director, did not meet the elements to be said as criminal act of corruption.